Critical Analysis of Narrative Research (Research, Society and Development, 2021)
The continuous development of theoretical and methodological approaches allows new ideas about the empirical reality. The narrative approach allows capturing the relevant actors, their multiple motivations, interests, activities and an interaction between the various contextual elements, thus providing an essential element for understanding the various types of processes. A basis for evidence is needed about how narrative methods can add value to more conventional forms of inquiry. The present research identifies itself as a strategy associated to the qualitative approach, since it is studied about the narrative research from a critical analysis of the bibliographical survey carried out in international books and journals. Thus, we sought to demonstrate the depth and scope of the contribution of narrative research. This research addresses as a key theme what characterizes the development of narrative research, making a historical conceptualization and dealing with the approach of narrative research, types of data collection and a critical analysis of narrative research.